Running from (with) mom guilt: exploring experiences of being a mother and training for and running marathons. Issue 2 (3rd April 2021) - Bean, Corliss; Wimbs, Raisa-Lee
ABSTRACT: Mothers tend to make sacrifices within their family role, including their physical activity levels. The purpose of this exploratory study was to understand how mothers balanced the roles of being a mother and training for and competing in a marathon, including the strategies used and barriers experienced. Eight mothers (Mage = 36.75), with children under 8 years old, participated in two semi-structured interviews (during training, post-race). Inductive thematic analysis resulted in the creation of two inter-related themes: (a) identity conflict and (b) balancing strategies. Specifically, identity challenges including: being a runner before mother, managing multiple identities, and feelings of guilt for not prioritizing the mother identity. Strategies were identified that helped minimize feelings of guilt and perceived lack of time: self-compassion, eliciting social support, and comprehensive planning. Findings from this study can advance academic literature and help inform training programs for women who are navigating motherhood.